Parental mediation of children's digital technology use in Singapore. Issue 1 (2nd January 2017) - Shin, Wonsun; Li, Benjamin
Abstract: This study examines parental mediation of children's digital technology use and factors associated with it. A survey of 557 parents of primary school children in Singapore revealed that parents tend to utilize simpler mediation strategies to supervise and control their children's digital technology use. Findings also suggest that parental mediation is more a function of parents' usage of digital technology and parent–child interaction patterns rather than parent–child demographic characteristics.